Justice for Women in Divorce Cases before the Religious Courts of Southeast Sulawesi: Feminist and Legal Pluralist Perspectives - Hakim, Guswan; Heryanti, Heryanti; Nur, Jabal; Suwarti, Suwarti; Abdul Jalil, Siti Misnar (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study examines the legal construction of contested divorce within Indonesia's Religious Court system through the analytical lenses of feminist legal theory and legal pluralism. It argues that contested divorce represents the institutional adaptation of Islamic family law within the national legal system and has significant implications for women's legal rights and access to justice. Employing an empirical legal research approach, the study integrates the analysis of legal norms with the realities of judicial practice in the Religious Courts of Southeast Sulawesi. The research draws upon feminist legal theory and legal pluralism as its principal theoretical frameworks. Data were collected through document analysis and semi-structured interviews. Documentary sources included Religious Court divorce statistics, statutory regulations, judicial decisions, scholarly books, and peer-reviewed journal articles, while interviews were conducted with Religious Court judges and legal scholars from universities in Southeast Sulawesi. The findings demonstrate that the increasing prevalence of contested divorce reflects women's growing legal consciousness and their willingness to assert their rights through formal judicial mechanisms.  Rather than occupying a passive position within marital relationships, women increasingly utilize legal institutions to challenge unequal or harmful marriages, indicating that the Religious Court system has become a more accessible avenue for seeking justice. In this respect, contested divorce may be understood as a positive indicator of expanding access to justice. although it simultaneously reveals persistent structural inequalities within marriage and the broader legal system. From the perspective of Islamic law, the institutionalization of contested divorce represents a process of normative adaptation through which the Religious Courts have reinterpreted classical Islamic legal principles in light of contemporary demands for justice, legal protection, and gender equality. Viewed through the framework of legal pluralism, the study further finds that contested divorce emerges from the interaction among state law, Islamic law, and customary (adat) law.